THE USE OF FAIRYTALE FILMS IN TEACHING NARRATIVE WRITING - Fauzia Rachmawati (Journal of English and Education, 2017)
This study entitled “The Use of Fairytale Films in Teaching Narrative Writing” was aimed to know whether or not the use of fairytale films can help the students improve their writing and to find out their responses to the teaching program. This study employed a quasi-experimental research design in which two classes of grade eight students in one junior high school in Bandung were chosen as experimental group and control group. Two types of test (pretest and posttest) and questionnaire were used as data collection techniques. Utilizing Jacob’s scoring rubric (1981), the students’ tests were graded and calculated using IBM SPSS 17.0. The result revealed that the experimental group that was given fairytale films shows significant improvement compared to the control group. The result from the questionnaire also showed that the students displayed excitement in learning when the treatment was given.